What and Who Are “Essential”? A Disability Justice Perspective on COVID-19 Measures and the Diverse Disability Communities in Ontario - Chavon Ann Niles; Mary Jean Hande; Ann Fudge Schormans; Wendy Porch; Susan Mahipaul; Jheanelle Anderson; Karen Yoshida (Studies in Social Justice)
Central to Ontario’s COVID-19 response was defining, supporting, and protecting essential services and, by extension, essential people – often through decision-making processes that were ad hoc and lacking in meaningful public engagement. This paper examines the Ontario government’s public health responses to the COVID-19 pandemic, from the early steps taken in 2020 by provincial officials to develop a triage protocol for hospitals that would discriminate against those who fall outside of the narrow view of essential people – especially disabled and older people – to the implementation of public health measures that also disadvantaged diverse disability communities in a multitude of settings and far-reaching, multiple, and intersecting ways. Selectively drawing on online local and national newspapers across Canada that mentioned COVID-19 and people with disabilities from March 2020 to June 2020, we examined the ways in which disabled people have been rendered invisible, invaluable, disposable, and “non-essential” as they struggle to survive the pandemic largely outside of provincial COVID-19 response frameworks. Through this analysis, we craft a contrasting understanding of “essential” that attends to the principles of disability justice, shifting interdependencies, and the diversity and mutuality of human needs. Drawing on examples of mutual aid and caregiving in diverse disabled communities, we also explore disability justice as an alternative framework that leaves no one behind.